# Functional Programming - Lambda Calculus

Lambda calculus is a framework developed by Alonzo Church in 1930s to study computations with functions.

**Function creation**− Church introduced the notation**λx.E**to denote a function in which ‘x’ is a formal argument and ‘E’ is the functional body. These functions can be of without names and single arguments.**Function application**− Church used the notation**E**to denote the application of function_{1}.E_{2}**E**to actual argument_{1}**E**. And all the functions are on single argument._{2}

## Syntax of Lambda Calculus

Lamdba calculus includes three different types of expressions, i.e.,

E :: = x(variables)

| E_{1} E_{2}(function application)

| λx.E(function creation)

Where **λx.E** is called Lambda abstraction and E is known as λ-expressions.

## Evaluating Lambda Calculus

Pure lambda calculus has no built-in functions. Let us evaluate the following expression −

(+ (* 5 6) (* 8 3))

Here, we can’t start with '+' because it only operates on numbers. There are two reducible expressions: (* 5 6) and (* 8 3).

We can reduce either one first. For example −

(+ (* 5 6) (* 8 3)) (+ 30 (* 8 3)) (+ 30 24) = 54

## β-reduction Rule

We need a reduction rule to handle λs

(λx . * 2 x) 4 (* 2 4) = 8

This is called β-reduction.

The formal parameter may be used several times −

(λx . + x x) 4 (+ 4 4) = 8

When there are multiple terms, we can handle them as follows −

(λx . (λx . + (− x 1)) x 3) 9

The inner **x** belongs to the inner **λ** and the outer x belongs to the outer one.

(λx . + (− x 1)) 9 3 + (− 9 1) 3 + 8 3 = 11

## Free and Bound Variables

In an expression, each appearance of a variable is either "free" (to λ) or "bound" (to a λ).

β-reduction of **(λx . E)** y replaces every **x** that occurs free in **E** with **y**. For Example −

## Alpha Reduction

Alpha reduction is very simple and it can be done without changing the meaning of a lambda expression.

λx . (λx . x) (+ 1 x) ↔ α λx . (λy . y) (+ 1 x)

For example −

(λx . (λx . + (− x 1)) x 3) 9 (λx . (λy . + (− y 1)) x 3) 9 (λy . + (− y 1)) 9 3 + (− 9 1) 3 + 8 3 11

## Church-Rosser Theorem

The Church-Rosser Theorem states the following −

If E1 ↔ E2, then there exists an E such that E1 → E and E2 → E. “Reduction in any way can eventually produce the same result.”

If E1 → E2, and E2 is normal form, then there is a normal-order reduction of E1 to E2. “Normal-order reduction will always produce a normal form, if one exists.”